Patrimônio cultural e capital urbano: disputas em torno dos legados industriais - Carvalho, Mônica de; Gagliardi, Clarissa; Marins, Paulo César Garcez (Cadernos Metrópole, 2024)
DOI: https://doi.org/10.1590/2236-9996.2025-6268275-pt https://doi.org/10.1590/2236-9996.2025-6268275-en